Pengaruh Belanja Modal, Dana Alokasi Umum dan Pertumbuhan Ekonomi Terhadap Pendapatan Asli Daerah Kota Medan 2015-2024 (Studi Kasus Pada Kota Medan) - Halawa, Risman; Masyitah, Emi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to determine the effect of capital expenditure, general allocation funds, and economic growth on Medan City's original regional revenue (PAD) from 2015 to 2024 (a case study in Medan City). This study uses a quantitative approach. The data source used in this study is secondary data, based on financial reports. The population used in this study is the Medan City financial realization report for 2015 to 2024, and a sample size of 40 people was used. Based on the results of the t-test, the criteria contained in the hypothesis test were accepted. The basis for the partial test conditions was already known, H1 was accepted, meaning that capital expenditure had a positive and significant effect on original regional revenue (PAD) with a calculated t value of 4.704 > t table 2.026. The general allocation fund (DAU) variable was found to have no positive and significant effect on original regional revenue (PAD), with a value of -1.255 < t table 2.026, meaning H2 was rejected. The economic growth variable did not have a positive and significant effect on local revenue (PAD), with a t-value of 1.378 < t-table of 2.026, indicating that H3 was rejected. The simultaneous test revealed that capital expenditure (X1), general allocation funds (X2), and economic growth (X3) collectively had a positive and significant effect on local revenue (PAD) at the Medan City Revenue Office.